The Socialization of Culturally Related Values and Prosocial Tendencies Among Mexican‐American Adolescents. Issue 6 (7th November 2016) - Knight, George P.; Carlo, Gustavo; Mahrer, Nicole E.; Davis, Alexandra N.
Abstract : The socialization of cultural values, ethnic identity, and prosocial behaviors is examined in a sample of 749 Mexican‐American adolescents, ages 9–12; M ( SD ) = 10.42 years (.55); 49% female, their mothers, and fathers at the 5th, 7th, and 10th grades. Parents' familism values positively predicted their ethnic socialization practices. Mothers' ethnic socialization positively predicted adolescents' ethnic identity, which positively predicted adolescents' familism. Familism was associated with several types of prosocial tendencies. Adolescents' material success and personal achievement values were negatively associated with altruistic helping and positively associated with public helping but not their parents' corresponding values. Findings support cultural socialization models, asserting that parents' traditional cultural values influence their socialization practices, youth cultural values, and youth prosocial behaviors.